Pengaruh Frekuensi Pengolahan Tanah dan Pupuk Kompos terhadap Sifat Fisik Tanah dan Hasil Jagung - DHARMA, I PUTU; PUJA, I NYOMAN (Agrotrop : Journal on Agriculture Science; Vol 9 No 2 (2019), 2019)
The Effect of Soil Tillages Frequency and Compost Fertilizer on Soil Physical Properties and Corn Yields. The aims of this research is to determine of effect soil tillage frequency and compost fertilizer on soil physical properties and corn yields. The method was used a Randomized Block Design (RBD), factorial consisting of two factors, namely: Soil Tillages Frequency (T) consists of 3 levels, namely: T0 = no tillage; T1 = if one time and T2 = if twice. Compost Fertilizer (K) consists of 3 levels, namely: K0 = Without compost, K1 = 5 tons compost/ha and B2 = 10 tons compost/ha. Combination treatment into 9 treatments, namely T0K0 , T0K1, T0K2, T1K0, T1K1, T1K2, T2K0, T2K1, T2K2. and each treatment was repeated 3 times, so there were 27 research plots.The results showed that the soil tillage frequency and compost fertilizer had no significant effect on the soil physical properties and corn yields. Twice soil tillage frequency resulted bulk density, porosity, soil moisture content and dry corn yields respectively 1.01 g/cm3, 60.98%, 37.31% and 0.83 kg/m2, and not significant different compared with no tillage which is 1.03 g/cm3, 60.43%, 36.57% and 0.81 kg/m2. Addition of 10 tons compost/ha resulted bulk density, porosity, soil moisture content and dry corn yield respectively 0.99 g/cm3, 61.75%, 38.21% and 0.86 kg/m2, and not significant different compared with without compost fertilizer which is 1.06 g/cm3, 59.40%, 36.44% and 0.80 kg/m2.